Los atributos culturales y los contextos de aprendizaje, un continuum socioeducativo. - Gómez, Máximo; Cando, Fabiola; Moyano, Sara (My University, 2019)
The main aim of this research was to determine the incidence of cultural attributes in the educational process from a socio-educational reading, a purpose that was deployed in the Rioblanco Alto Educational Unit and the Fausto Espinoza Pinto School of Basic Education. The research corresponds to a qualitative and quantitative approach of exploratory level. The qualitative data were correlated with quantitative data to explain, with a transdisciplinary approach, the empirical manifestations of the subject. The methodological strategy used was based on the bibliographical review, scientific observation, interview, the survey and a hermeneutical analysis for the understanding of the information. The data show that cultural attributes are obviated in the teaching-learning process, which creates a hegemony that ignores the potentialities of cultural diversity of students; behavior that produces a process of acculturation that fractures the identity of the actors who carry symbolization and ancestral knowledge. This effect has as its origin the reduced dimension of the cultural competences of the teachers who do not know the pedagogical procedure to strengthen this feature of the identity.
El objetivo de esta investigación fue determinar la incidencia de los atributos culturales en el proceso educativo desde una lectura socioeducativa, propósito que se desplegó en la Unidad Educativa Rioblanco Alto y la Escuela de Educación Básica Fausto Espinoza Pinto. La investigación corresponde a un enfoque cuali y cuantitativo de nivel exploratorio. Los datos cualitativos diagnosticados se correlacionaron con datos cuantitativos para explicar con un enfoque transdisciplinario, las manifestaciones empíricas del tema. La estrategia metodológica empleada se basó en la revisión bibliográfica, la observación científica, la entrevista, la encuesta y un análisis hermenéutico para la comprensión de la información. Los datos muestran que los atributos culturales son obviados en el proceso de enseñanza-aprendizaje lo cual crea una hegemonía que ignora las potencialidades de la diversidad cultural de los estudiantes; comportamiento que produce un proceso de aculturación que fractura la identidad de los actores portadores de la simbolización y el conocimiento ancestral. Este efecto tiene como origen la reducida dimensión de las competencias culturales de los docentes quienes desconocen el procedimiento pedagógico para fortalecer este rasgo de la identidad.
Keywords: ATRIBUTOS CULTURALES; PROCESO DE ENSEÑANZA-APRENDIZAJE